IDENTIFIKASI LALAT BUAH (Diptera: Tephritidae) PADA KEBUN JERUK DI KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Fitriani, Via; Karno, Ria; Bharmana, Eti Meirina (Sainstek : Jurnal Sains dan Teknologi, 2018)
This research aims to determine species of fruit flies (Diptera: Tephritidae) the attacking orange plantion Rambah Samo District Rokan Hulu Regency. Study was conducted in March to May 2018, using a survey method with technique sampling purposive sampling. The research found 6 species with a total of 236 individuals. The species is Bactrocera umbrosa, B. Carambolae, B. Papayea, B. dorsalis, B. caudata and  B. albistrigata. Fruit fly species most widely found was B. carambolae the total number of 80 individiuals, whereas B. umbrosa total number of 24 individual, B. Papayea total number 48 individual, B. dorsalis total number of 7 individual, B. caudata total number of 74 individual, B. albistrigata total number of 3 individual.